Discussion on the Development of Space-Based Information Systems of America - Zhongyu MIAO; Xiaogeng HOU; Hanyu ZHENG; Yuanyuan HAO (天地一体化信息网络)
Space-based information system has the absolute high-level advantage of the battlefi eld, is not limited by regional boundaries and does not rely on air and sea domination.It has the strategic advantage of comprehensively providing battlefi eld information support, breaking geographical restrictions and realizing the wide area interconnection of various services and weapons.It has become an indispensable element of the future battlefi eld.In view of the capability requirements of future global operations for space-based information networks, the forefront of America was focused on.The research progress of space-based information system construction and reported the research progress of typical systems such as the next generation of overhead persistent infrared program (Next-Gen OPIR), the space link-16 program, the Blackjack program, and the commercial augmented space inter-networked operations (CASINO) program were analyzed.The prospective development tendency of space-based information systems of America was summarized, after which some suggestions were put forward for the construction of spacebased information system of our country.